Education for environmental ethics in forest areas - the Leave No Trace idea: Concept of education for environmental ethics on forest areas: The Leave No Trace idea - Płoskonka, Przemysław (Studia Ecologiae et Bioethicae, 2019)
The article is characterised by a popular concept in the world of education for environmental ethics (ethics outdorowa): Leave No Trace. Initially, the programme was directed mainly toward environments associated with the mountain-guides, climbers and hikers in response to devastation and littering. Now, it has been extended to other natural areas, including the environment as a whole. As a model of environmental ethics (outdoor), Leave No Trace promotes responsible attitude (raising awareness). The core of the concept is based on the seven universal principles, which, in combination with transferred knowledge and acquired skills, are designed to minimise human impact on the natural environment.